Functional and mechanical properties of corn starch-based and potato starch-based edible films - De Gala, Christa Zapanta; Cornago, Djanna F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
The functional properties (color, opacity, thickness, water vapor permeability, and water absorption capacity) and mechanical properties (tensile strength and ultimate elongation) of corn starch-based edible film (CSEF) and potato starch-based edible film (PSEF) were evaluated and compared. The edible film which exhibited better functional and mechanical properties was compared to hog casing. Between the two starch-based edible films, the CSEF was better in terms of water vapour permeability (WVP) (4.7242 g (m hr kPa)-1) and water absorption capacity (WAC) (0.26725 and 0.31550 at 2 hours and 26 hours, respectively). However, PSEF was better in terms of color because of its lower b* value (3.625) compared to CSEF (4.385). Functional and mechanical properties of CSEF were compared to those of hog casing. Results showed that the edible film had better opacity (30.745%), thickness (0.0430mm), and WVP (4.7242 g (m hr kPa)-1), making it a good alternative to hog casing as sausage casing. However, the potential of corn-starch based film as sausage casing is only realized when its mechanical properties and properties specific for sausage casings are further improved or enhanced.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Edible coatings -- Philippines; Food -- Packaging